2013
DOI: 10.1103/physrevc.87.064613
|View full text |Cite
|
Sign up to set email alerts
|

Rapid convergence of the Weinberg expansion of the deuteron stripping amplitude

Abstract: Theories of (d, p) reactions frequently use a formalism based on a transition amplitude that is dominated by the components of the total three-body scattering wave function where the spatial separation between the incoming neutron and proton is confined by the range of the n-p interaction, V np . By comparison with calculations based on the continuum discretized coupled channels method we show that the (d, p) transition amplitude is dominated by the first term of the expansion of the three-body wave function i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Following Johnson-Tandy [2] we retain only the first Weinberg component of the A + n + p system in the (d, p) transfer amplitude since this amplitude is sensitive only to those parts of this wave function in which the neutron n is close to the proton p. Recently, exact continuum-discretized coupled channel calculations confirmed that this component indeed dominates [26]. The first Weinberg component is a product of the deuteron wave function φ 0 (r) times the d − A relative motion wave function χ(R) which is the solution of the twobody Schrödinger equation with an adiabatic potential constructed from p − A and n − A optical potentials.…”
Section: The Deuteron-target Potential For (D P) Reactions In Tmentioning
confidence: 99%
“…Following Johnson-Tandy [2] we retain only the first Weinberg component of the A + n + p system in the (d, p) transfer amplitude since this amplitude is sensitive only to those parts of this wave function in which the neutron n is close to the proton p. Recently, exact continuum-discretized coupled channel calculations confirmed that this component indeed dominates [26]. The first Weinberg component is a product of the deuteron wave function φ 0 (r) times the d − A relative motion wave function χ(R) which is the solution of the twobody Schrödinger equation with an adiabatic potential constructed from p − A and n − A optical potentials.…”
Section: The Deuteron-target Potential For (D P) Reactions In Tmentioning
confidence: 99%
“…These constraints follow from the ones in the original matrix element (33). Replacing the exact scattering wave function Ψ has not yet been reached.…”
Section: Standard Choice Of the Exit Channel Wave Functionmentioning
confidence: 99%
“…The first correct proof of Eq. (49) was presented by Goldberger and Watson [29] and extensively used by Johnson and coworkers in the formulation of the ADWA and its applications [26,[30][31][32][33].…”
Section: B Prior Formmentioning
confidence: 99%
See 1 more Smart Citation
“…In three-body models of the (d, p) and (p, d) reactions proton and neutron potentials are used instead of the deuteron-target potentials [25][26][27]. The deuteron-target OMPs are necessary in many other reactions, for instance, the ( 3 He, d) reactions, for which the distorted wave Born approximation is usually still valid [28,29].…”
Section: Introductionmentioning
confidence: 99%